Dominance of particulate organic carbon in top mineral soils in cold regions [Dataset] - García-Palacios, Pablo (Figshare, 2024)
Template_experimental contains the experimental warming and POC and MAOC data in cold vs other biomes .-- Template_observational contains the observational POC and MAOC data across cold regions. Peer reviewed